2019
DOI: 10.1016/j.bja.2019.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and consensus definitions for the Standardised Endpoints in Perioperative Medicine initiative: clinical indicators

Abstract: Background: Clinical indicators are powerful tools to quantify the safety and quality of patient care. Their validity is often unclear and definitions extremely heterogeneous. As part of the International Standardised Endpoints in Perioperative Medicine (StEP) initiative, this study aimed to derive a set of standardised and valid clinical outcome indicators for use in perioperative clinical trials. Methods: We identified clinical indicators via a systematic review of the anaesthesia and perioperative medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 20 publications
0
43
0
5
Order By: Relevance
“…The overall methodology was similar to previously published StEP projects. 6,7 We undertook a systematic review of noncardiac perioperative clinical trials (2005e17). The StEP Steering Committee had made the decision in 2015 to review the last 10 yr of perioperative literature, such that the first year reviewed was 2005.…”
Section: Methodsmentioning
confidence: 99%
“…The overall methodology was similar to previously published StEP projects. 6,7 We undertook a systematic review of noncardiac perioperative clinical trials (2005e17). The StEP Steering Committee had made the decision in 2015 to review the last 10 yr of perioperative literature, such that the first year reviewed was 2005.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 599 outcomes extracted, the top three outcome domains were patient comfort (49%), clinical indicators (16%), and (19) 136 (47) 1353 (62) 293 (49) 1805 57Patient-centered outcomes (%) 6 (5) 35 (12) 251 (12) 86 (14) 378 (12) Bleeding/transfusion (%) 3 318 (6) 57(3) 32 (5) 110 3Healthcare utilization (%) 10 (8) 21 7189 (9) 60 (10) 280 (9) Clinical indicators (%) 44 3761 (21) 245 (11) 93 (16) 443 14Other (%) 34 2821 786 4 Table 6).…”
Section: Adolescents (≥13-year-olds)mentioning
confidence: 99%
“…perioperative care6 which include clinical indicators,19 patient comfort,20 patient-centered outcomes,21 infection and sepsis,22 renal end points,23 postoperative cancer outcomes,24 blood loss and transfusion,25 and pulmonary complications, 26. While pediatric perioperative trials frequently reported outcomes in the patient comfort and clinical indicators domains, some of the additional domain outcomes are less Hemodynamic/vital signs/laboratory 23 ECG, blood pressure, oxygen saturation, endtidal CO 2 , heart rate and mean arterial pressure before and after fluid challenge, urine values, blood glucose, postoperative acid base (serum pH, Base deficit, serum bicarbonate, anion gap), metabolic (free fatty acid, beta-hydroxybutyrate, serum lactate), serum electrolytes (sodium, potassium, calcium), liver function (liver biopsy, AST/ALT, ALP, GGT), endocrine (serum insulin, glucagon, cortisol, glucagon/insulin ratio) Reported perioperative outcomes for the infant subpopulation…”
mentioning
confidence: 99%
“…Final recommendations are based on identifying items critical for inclusion, plus rating the face and content validity, reliability, and feasibility of the specific endpoints or measurement tools to establish the Core Outcome Measures in Perioperative and Anaesthetic Care (COMPAC) . Results have been published across several predetermined domains that include clinical indicators, infection and sepsis, renal endpoints, postoperative cancer outcomes, pulmonary complications, blood loss and transfusion, patient comfort, and patient‐centered outcomes …”
Section: The Need For Core Outcome Sets For Pediatric Perioperative Carementioning
confidence: 99%
“…In addition to differing from adults, outcomes within pediatric practice may require consideration of specific age‐based subpopulations. In adults, ischemic heart disease and myocardial infarction are important cardiovascular outcomes, whereas congenital heart disease influences mortality, risk of perioperative cardiac arrest, and potential clinical indicators such as unplanned intensive care admission in children. Readmission is a core clinical indicator, but reasons for rehospitalization after discharge also differ between adults and children…”
Section: The Need For Core Outcome Sets For Pediatric Perioperative Carementioning
confidence: 99%